Scheduling of inspectors for ticket spot checking in urban rail transportation - Thorlacius, Per; Clausen, Jens (Proceedings from the Annual Transport Conference at Aalborg University, 2008)
A central issue for operators of passenger transportation in urban rail is balancing the income from tickets against the cost of the operation. The main part of the income except for gov- ernmental subsidies comes from sales of tickets. There are various ways to ensure that all passengers carry valid tickets, i.e. to avoid so called fare evasion. Many European companies use spot checking of passengers and among these is DSB S-tog. The current paper describes a decision support tool developed at DSB S-tog. Based on historical data regarding when penalty fares are claimed and based on the schedules of the inspectors, this tool enables the construction of new schedules for tickets inspectors, so that the income from penalty fares claimed from passengers without a valid ticket is maximised. Other tools to increase income from ticket sales and penalty fares are also discussed.